2014
DOI: 10.11604/pamj.2014.19.278.5202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the notifiable diseases surveillance system in sanyati district, Zimbabwe, 2010-2011

Abstract: IntroductionThe Notifiable disease surveillance system (NDSS) was established in Zimbabwe through the Public Health Act. Between January and August 2011, 14 dog bites were treated at Kadoma Hospital. Eighty-six doses of anti-rabies vaccine were dispensed. One suspected rabies case was reported, without epidemiological investigations. The discrepancy may imply under reporting of Notifiable Diseases. The study was conducted to evaluate the NDSS in Sanyati district.MethodsA descriptive cross sectional study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(79 citation statements)
references
References 3 publications
5
74
0
Order By: Relevance
“…In a similar study done by Maponga et al (2011) in Sanyati district low knowledge was attributed to lack of training [5]. Maponga et al (2011) stated that low knowledge can result in health workers having a low index of suspicion of cases or failing to report notifiable diseases [5]. In Beitbridge district, Juru et al (2015) also found out that not knowing the right form to use can have a resultant negative bearing on ability to notify diseases of public health importance [6].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In a similar study done by Maponga et al (2011) in Sanyati district low knowledge was attributed to lack of training [5]. Maponga et al (2011) stated that low knowledge can result in health workers having a low index of suspicion of cases or failing to report notifiable diseases [5]. In Beitbridge district, Juru et al (2015) also found out that not knowing the right form to use can have a resultant negative bearing on ability to notify diseases of public health importance [6].…”
Section: Discussionmentioning
confidence: 63%
“…It is essential that health workers are knowledgeable on the surveillance system so that they are able to identify, correctly diagnose and timeously notify notifiable diseases as this assists in prompt disease investigations and control, thereby minimising outbreaks. In a similar study done by Maponga et al (2011) in Sanyati district low knowledge was attributed to lack of training [5]. Maponga et al (2011) stated that low knowledge can result in health workers having a low index of suspicion of cases or failing to report notifiable diseases [5].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several studies in the African context including Zimbabwe have linked lack of knowledge to not having being trained or inducted in the surveillance system [6]- [10]. It is therefore possible that the poor knowledge revealed in this study could be due lack of training.…”
Section: Discussionmentioning
confidence: 90%
“…Similar to our finding Maponga et al (2011) found that knowledge was low amongst health workers in Sanyati District. According to Maponga et al (2011) lack of knowledge can result in health workers having a low index of suspicion of cases of Notifiable diseases or failing to report Notifiable diseases, resulting in delayed investigations and control of outbreaks [6]. Bawa S.B, et al (2003), in an evaluation of the Notifiable Disease Surveillance System in Nigeria, also found that knowledge was low amongst health workers with only 38% having heard about the NDSS [7].…”
Section: Discussionmentioning
confidence: 99%